Effect of mega floral booster addition on carcass characteristics of quail meat - Ahmad Syazni, K.; Sharif, U.H.; Kamarudin, A.S.; Huda, N. (2019)
This study evaluated the effect of Mega Floral Booster (MFB) as probiotic supplement on the carcass yield and physicochemical properties of quail meat. The treatment is divided to four treatments based on percentage of MFB include MFB-0.00 (control), MFB-0.05 (0.05% of MFB), MFB-0.20 (0.20% of MFB) and MFB-0.35 (0.35% of MFB). The 18 of quail species Cortunix japonica (Japanese quail) used as the main material in the study for each treatments. For the first until fourteen days, the quails are supplied with commercial feed only. After fifteen days, the quails begin provided with the MFB-0.00, MFB-0.05, MFB-0.20 and MFB-0.35 mixed with commercial feed. The quails for 42 days slaughtered and deboned of breast and whole leg separated from the bone for analysis. Probiotic supplement (Mega Floral Booster) had no influence on body weight, and carcass characteristics (breast, whole leg muscle and carcass yield) (p>0.05). MFB-0.20 had influence on color parameter (L∗, a∗ and b∗), pH and WHC of quail meats compared to MFB-0.00 (p<0.05). MFB show cooking loss, juiciness and Warner-Bratzler shear force not affected by treatment. Thus, Mega Floral Booster is not affecting the quality of quail meats.